Occurrence of Escherichia coli in Wildlife from Different Habitats of Sarawak, Malaysia - Lesley Maurice, Bilung; Kho, Kai Ling; Kasing, Apun; Mohd Tajuddin, Abdullah; Mustapha, Abdul Rahman; Chen, Yik Ming; Adom, Benjamen; Yee Ling, Chong; Hashimatul Fatma, Hashim (Borneo Journal of Resource Science and Technology, 2014)
This study was carried out to assess the occurrence of Escherichia coli (E. coli) in the bats, birds and rodents as representative of wildlife from different habitats in Sibu and Kapit, Sarawak, Malaysia. A total of 682 swab samples were collected from wildlife hosts and screened for the bacteria E. coli and E. coli O157:H7 using standard microbiological methods and molecular techniques. The overall occurrence rates of E. coli among these hosts were 14%, 17% and 54% for bats, birds and rodents, respectively. The occurrence of E. coli was the highest in rodents regardless of the habitats. Isolated E. coli were then screened for E. coli O157:H7 by using a multiplex PCR with four primer pairs targeting for Shiga toxin producing genes (slt-I and slt-II), and the genes involved in biosynthesis of O157 antigen (rfbE) and H7 antigen (fliCH7 ). slt-I, slt-II and rfbE genes were not detected in any of the E. coli isolates. However, the gene encoding for H7 antigen was detected in 23 E. coli isolates. This indicated that E. coli O157:H7 strain was not detected in the wildlife studied. Absence of E. coli O157:H7 in the wildlife studied indicated these wild animals do not serve as an important reservoir of E. coli O157:H7. However, precautions have to be taken as other group of pathogenic E. coli may pose a zoonotic risk for humans and other animals.